1996
DOI: 10.1002/j.2161-1920.1996.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between a Feminist Approach to Career Counseling and Career Self‐Efficacy Beliefs

Abstract: To determine whether liberal feminist and conventional approaches to career counseling might differentially affect women's career self‐efficacy beliefs, 40 college women heard audiotapes of career counseling and provided ratings of their own career self‐efficacy. Analysis supported the suggestion that a feminist approach to career counseling can have a significantly more positive effect on career self‐efficacy than a conventional approach. This was true for ratings on the category of nontraditional careers as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Students who par-ticipated in the delayed-treatment control group also reported greater CDMSE, but not as high as the first treatment control group. Similar to Juntunen (1996), Foltz and Luzzo concluded that the results of their study provided support for the necessity of counselors "to move beyond mere assessment of career interests and skills to thoroughly examine the process of career development relative to the client" (p. 42). Sullivan and Mahalik (2000) studied the effectiveness of a 6-week group counseling approach that incorporates the four sources of self-efficacy and attends to contextual factors (i.e., societal messages) with a sample of college women having moderate to high levels of career indecision.…”
Section: Experimental and Quasi-experimental Design Studiesmentioning
confidence: 74%
“…Students who par-ticipated in the delayed-treatment control group also reported greater CDMSE, but not as high as the first treatment control group. Similar to Juntunen (1996), Foltz and Luzzo concluded that the results of their study provided support for the necessity of counselors "to move beyond mere assessment of career interests and skills to thoroughly examine the process of career development relative to the client" (p. 42). Sullivan and Mahalik (2000) studied the effectiveness of a 6-week group counseling approach that incorporates the four sources of self-efficacy and attends to contextual factors (i.e., societal messages) with a sample of college women having moderate to high levels of career indecision.…”
Section: Experimental and Quasi-experimental Design Studiesmentioning
confidence: 74%
“…However, we did find that having self‐efficacy beliefs, holding feminist attitudes, and identifying as female (i.e., Steps 1 and 2 of the moderation models) linearly predicted educational aspiration for our sample. In light of these findings, career counselors can promote college students' empowerment by encouraging them to take responsibility for their own educational goals (Juntunen, 1996). We invite career counselors to develop college fairs so that students can receive information about advanced degrees from representatives or professionals within their related fields.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that selfefficacy influenced one's educational and occupational aspirations (Bandura et al, 2001;Chang, 1990), career choice and management (Bandura et al, 2001;Dawes et al, 2000;Hackett and Betz, 1981;Juntunen, 1996), and educational and occupational attainment (Ancis and Phillips, 1996;Chang, 1990;Wang et al, 1999). Fiorentine (1988) found that female premedical students' lower confidence in performing the role of physician explained the high attrition rate of female students in premedical programs.…”
Section: Theoretical Frameworkmentioning
confidence: 98%